Risk Factors of Physical Condition of House Against Malaria Occurrence in Ende East Nusa Tenggara Indonesia - MARIA SALESTINA SEKUNDA; ANATOLIA KARMELITA DOONDORI (Poltekkes Kemenkes Kupang, 2017)
Introduction: Malaria is a health problem in Eastern Indonesia, especially in the East Nusa Tenggara. In 2014 there was a mass distribution of insecticide-treated nets but the incidence of malaria is still high. This study identified the physical condition of the house against the malaria occurrences. Methods: A case-control study with 67 cases and 134 control subjects was conducted in the District Wewaria Ende in 2016. The data of the physical condition of the house includes conditions of the walls, floors windows, ventilation, ceiling and lighting were obtained through observation method and subjective measuring. The data were analyzed by multivariate logistic regression. Results: The cases and control groups were comparable in terms of gender (p = 1), age (p = 0.9), education level (p = 0.9) and occupation (p = 0.6). There are three independent variables were identified as risk factors for malaria is the gloomy of lighting (OR 3.64; 95%CI = 1.77 to 7.47), moist floors (OR 3.02; 95%CI = 1.24 to 7.34) and damaged ceilings (OR 2.41; 95%CI = 1.02 to 5.72). Conclusion: The physical condition of houses are risk factors of malaria occurrence.